1994
DOI: 10.2337/diacare.17.12.1390
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Glycemic Control Has a Nonlinear Association to the Frequency of Background Retinopathy in Adolescents With Diabetes: Follow-up of the Berlin Retinopathy Study

Abstract: Two statistical models are appropriate to explain the relationship between glycemic control and risk for background retinopathy: 1) a continuous exponential relationship as described by the DCCT or 2) the presence of a threshold HbA1c level at 9%. Thus, diabetes treatment in children should aim at long-term HbA1c levels < 9.0%, but every progress closer to normal may further reduce the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 17 publications
10
54
0
2
Order By: Relevance
“…The strongest risk factors for retinopathy include glycemic control and diabetes duration, as most other studies have shown (19)(20)(21)(22)(23)(24). We also demonstrate that there is no glycemic threshold at which incidence of retinopathy escalates sharply, reflecting our cross-sectional findings (25) and other cohort studies (19,20,26). This is in contrast with a report of a glycemic threshold effect at 8%, based on a reevaluation of published data (6).…”
Section: No Datasupporting
confidence: 72%
“…The strongest risk factors for retinopathy include glycemic control and diabetes duration, as most other studies have shown (19)(20)(21)(22)(23)(24). We also demonstrate that there is no glycemic threshold at which incidence of retinopathy escalates sharply, reflecting our cross-sectional findings (25) and other cohort studies (19,20,26). This is in contrast with a report of a glycemic threshold effect at 8%, based on a reevaluation of published data (6).…”
Section: No Datasupporting
confidence: 72%
“…However, the absolute risk was very low below HbA 1c 8.0% (64 mmol/mol) (23). Other authors have suggested a glycemic threshold of HbA 1c of ;8-9% (65-75 mmol/mol) (24)(25)(26). A distinction should, however, be made between mild and severe diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 24 P , 0.001 for HbA 1c and grade of retinopathy and nephropathy. Data were analyzed using one-way ANOVA and Bonferroni post hoc test.…”
Section: Hba 1cmentioning
confidence: 99%
“…Animal studies of DR [148][149][150] , large randomised control trials (RCT) such as the DCCT [151][152][153] and epidemiological data 154;155 , emphasise the critical relationship between glycaemic control to the development and progression of DR. Chronic hyperglycaemia is now accepted as the common pathway leading to DR [156][157][158][159] .…”
mentioning
confidence: 99%